K0S K0S final state in two-photon collisions and implications for glueballs - Dova, María Teresa (2001)
The K0S K0S final state in two-photon collisions is studied with the L3 detector at LEP. The mass spectrum is dominated by the formation of the f '2(1525) tensor meson in the helicity-two state with a two-photon width times the branching ratio into K K of 76 ± 6 ± 11 eV. A clear signal for the formation of the fJ(1710) is observed and it is found to be dominated by the spin-two helicity-two state. No resonance is observed in the mass region around 2.2 GeV and an upper limit of 1.4 eV at 95% C.L. is derived for the two-photon width times the branching ratio into K0 SK0 S for the glueball candidate ξ (2230).